WORK OF MUSCLES RESPONSIBLE FOR THE FUNCTIONING OF THE FOOT IN CONDITIONS OF KNEE JOINT CONTRACTURE - Karpinska, Olena; Khaled, Obeidat (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Prolonged walking with knee joint contracture causes changes in the functioning of the muscles of the lower leg and foot. Objective. To study the functioning of the foot and leg muscles in the conditions of knee joint contracture using a human walking model. Methods. The gait analysis was performed in the OpenSim 4.0 program. The modeling was based on the gait2394 model. The following muscles were studied: m. peroneus brevis, m. peroneus longus, m. peroneus tertius, m. tibialis posterior, m. tibialis anterium, m. flexor digitorum longus, m. flexor hallucis longus, m. extensor digitorum longus, m. extensor hallucis longus. Results. Restriction of joint mobility leads to a redistribution of muscle strength. In conditions of 15° knee joint flexion contracture, support on the toes causes significant overstrain of the muscles responsible for the functioning of the lower leg, foot and toes. In particular, the m. peroneus brevis and m. peroneus longus are quite long, their function is impaired, but the required increase in strength is from 10 to 400 %, while the m. peroneus tertius (short), for foot flexion in some phases of the step, its strength increased threefold. Among the muscles of the lower leg, the greatest increase in isometric strength was required for the m. tibialis anterior compared to the m. tibialis posterior, which works mainly for foot extension. For the muscles responsible for flexion/extension of the toes in conditions of knee joint contracture, a significant, sometimes 3–5 times, increase in strength was necessary to perform the required function. Conclusions. Knee joint contracture leads to a change in the biomechanics of the entire lower extremity, namely, to an increase in changes in the functioning of the muscles responsible for the functioning of the foot, which work under such conditions with a constant increase in tension. Given the impact of knee joint contracture on the functioning of the muscles of the lower extremity, it is possible to predict the course of the pathological process, determine which muscle groups are most affected and which muscle group needs to be corrected before and after surgery.